Behçet Syndrome Associated with Protein S Deficiency - Chafa, O; Fischer, A M; Meriane, F; Chellali, T; Sternberg, C; Otmani, F; Benabadji, M (Thrombosis and Haemostasis, 1992)
Beçget syndrome is a multisystem disorder characterized by ocular, mucocutaneous, articular, gastrointestinal and neurologic abnormalities. We report here an unusual case of Beçget syndrome, characterized by the importance of the thrombotic events(7 phlebitis of both legs and resection of two toes). Additional manifestations of the Beçget syndrome occurred only 10 years after the first thrombotic episode. The oldest daugther of the propositus and his brother suffered also from thrombophlebitis; this familial history of thrombosis led to the performance of a haemostatic study. A congenital protein S deficiency was found in the propositus and in three of his children. Normal protein S levels were found in nine unrelated patients with Beçget syndrome. Thus this observation suggests that, when thrombotic manifestations are the first and major symptom of Beçget syndrom, an additional cause of thrombosis has to be investigated.